2019
DOI: 10.3390/ijms20164051
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Micro-Bleeds and Neuroinflammation in E19 Rat Fetuses Exposed to Utero-Placental Ischemia

Abstract: Offspring of preeclampsia patients have an increased risk of developing neurological deficits and cognitive impairment. While low placental perfusion, common in preeclampsia and growth restriction, has been linked to neurological deficits, a causative link is not fully established. The goal of this study was to test the hypothesis that placental ischemia induces neuroinflammation and micro-hemorrhages in utero. Timed-pregnant Sprague Dawley rats were weight-matched for sham surgery (abdominal incision only) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…We therefore propose that the elevated IL-6 is responsible, at least partially, for these effects ( Figure 6 ). This may have important implications for our understanding of the physiological relationship between pre-eclampsia and neurodevelopment in vivo , considering IL-6 is able to permeate both the human placenta and the blood-brain barrier ( Zaretsky et al, 2004 ; Banks, 2005 ), and IL-6 is correspondingly elevated in the circulation of human neonates born to pre-eclamptic pregnancies ( Tosun et al, 2010 ) and the brains of rat pups exposed to a pre-clinical model of PE ( Giambrone et al, 2019 ). This suggests IL-6 as a potential pathway for early therapeutic intervention, not to prevent the progression of PE in the mother, but to attenuate its deleterious effects on the fetal brain, although further preclinical and clinical studies will be required to discern this.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore propose that the elevated IL-6 is responsible, at least partially, for these effects ( Figure 6 ). This may have important implications for our understanding of the physiological relationship between pre-eclampsia and neurodevelopment in vivo , considering IL-6 is able to permeate both the human placenta and the blood-brain barrier ( Zaretsky et al, 2004 ; Banks, 2005 ), and IL-6 is correspondingly elevated in the circulation of human neonates born to pre-eclamptic pregnancies ( Tosun et al, 2010 ) and the brains of rat pups exposed to a pre-clinical model of PE ( Giambrone et al, 2019 ). This suggests IL-6 as a potential pathway for early therapeutic intervention, not to prevent the progression of PE in the mother, but to attenuate its deleterious effects on the fetal brain, although further preclinical and clinical studies will be required to discern this.…”
Section: Discussionmentioning
confidence: 99%
“…In preeclampsia and gestational marginal zinc deficiency studies, pregnant rats were sacrificed at E19 [44,45]. In the present study, pregnant rats were treated from E0 to E19, but we did not study the effects of drugs on fetal rats post E19.…”
Section: Plos Onementioning
confidence: 92%
“…A study demonstrated that the brain of fetuses extracted from RUPP model showed increased levels of proinflammatory cytokines, chemokines, higher incidence of microbleeds, and reduced microglial density in the subventricular zone, either excreted from the fetal brain or originating from maternal blood. 159 In another study, pregnant rats were treated with an inhibitor of nitric oxide synthase, the N-nitro-L-methylarginine, at different gestational ages to induce an early and late-onset preeclampsia-like state. 160 Under the above conditions, the cortical and cerebellar expression of 2 markers of neuroinflammation, was assessed in both mother and pups.…”
Section: Proposed Consequences Of Cerebral Vascular Alterations In Th...mentioning
confidence: 99%
“…A study demonstrated that the brain of fetuses extracted from RUPP model showed increased levels of proinflammatory cytokines, chemokines, higher incidence of microbleeds, and reduced microglial density in the subventricular zone, either excreted from the fetal brain or originating from maternal blood. 159…”
Section: Proposed Consequences Of Cerebral Vascular Alterations In Th...mentioning
confidence: 99%